11 "Green Means Go": Creation of a Discharge Checklist Tool for Patients with Bronchiolitis. (19th August 2020) - Buba, Melanie; Hall, Kerry-Lynne
Abstract: Background: A consistent and predictable discharge process is difficult to achieve, yet essential for good patient flow, appropriate resourcing, and safe patient care. At our institution, physicians predicted the estimated discharge date (EDD) for patients with bronchiolitis with 70.5% accuracy (January – March 2019). A key driver of this unpredictability is a lack of consensus on "medical discharge readiness" criteria across providers, which also has impacts on communication within the health care team and with patients and families. Objectives: 1. To improve the ability to predict discharge date for patients with bronchiolitis by implementing a standardized medical discharge criteria checklist tool for one month (April 2019). 2. To more fully engage nurses in their patients' care by improving transparency and accuracy of information about discharge. 3. To increase patient and family satisfaction with the discharge process. Design/Methods: Meetings with key stakeholders determined drivers of discharge. Data on national practice variation in the management of patients with bronchiolitis was reviewed and informed the creation of a set of medical discharge criteria. Criteria were reviewed and accepted by the Division of Pediatric Medicine and presented to key stakeholders for feedback. Patient inclusion and exclusion criteria were developed. Feedback on the intervention was sought via surveys to physicians, nurses and patients/families. Results: There was significant improvement (70.5% to 92.3%) in accuracy of predicting EDD with use of the medical discharge criteria checklist tool. There was also a reduction in length of stay. There were no patient bounce-backs to ED or patient readmissions. There was high satisfaction and support of the checklist tool from nursing and caregivers. Conclusion: The development of standardized medical discharge criteria for patients with bronchiolitis is a safe and effective way to improve predictability, transparency, communication and patient flow, while enhancing engagement of the health care team and patient and family satisfaction. Its use is also associated with a reduced length of stay. Future directions include integrating the checklist tool into the electronic health record and moving towards a nurse-facilitated discharge process. Exploring and addressing non-medical barriers to discharge should also be a priority.